PENGENALAN STANDAR MUTU DALAM INDUSTRI PANGAN DI PABRIK TAHU, DEPOK - Dahliyah Hayati; Trisna Yuniarti; Dian Adhe Bianggo (PUSAT PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT, POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN PALEMBANG, 2021)
Food that is guaranteed to be clean is one of the main factors in the success of humans in maintaining a healthy body. Not all small and medium-sized industries (IKM) understand the food quality standards that they must follow to ensure the cleanliness of their processed products. One of the main tasks of lecturers is to do community service, where through this community service program it is hoped that the knowledge possessed by lecturers can provide benefits not only for the world of education, but also the wider community including small and medium industry players. From the community service carried out by APP Jakarta Polytechnic lecturers in several IKMs, it is clear that industry players really need the transfer of knowledge about what good food quality standards look like and it can be concluded that the provision of material on good food quality standards (ISO 22000:2018) is not can be done only with 1-2 arrivals, but also required further assistance to get optimal results.